Advances in follow-up techniques for implantable defibrillators - Brachmann, Johannes; Sterns, Laurence D.; Hilbel, Thomas; Beyer, Thorsten; Schöls, Wolfgang; Freigang, Kirsten Dorothee; Melichercik, Juraj; Ruf-Richter, Jutta; Kübler, Wolfgang (American heart journal, 1994)
The complexity of newer implantable defibrillators has made device follow-up increasingly more intricate. Extensive data-logging capacity provides specific information on recorded events, which facilitates more accurate determination of patient arrhythmias. This helps the clinician judge whether the device is detecting and treating arrhythmias appropriately, or whether false sensing of external signals or supraventricular rhythms is occurring. There is also a record of the efficacy of delivered therapy from the device that helps in optimizing subsequent programming. Programming itself has become much more complicated, with multiple independently programmable therapy zones, each with numerous available therapeutic modalities. In addition, defibrillator status information has been improved. Accurate battery voltage measurements give a reasonable estimate of remaining device life, and pace/sense and shock lead impedances can be measured to provide information on total system integrity. Together, these advances allow more specific programming of the device to the individual patient's condition but require increasing experience and expertise of the physician.
Elektronische Reproduktion der Druck-Ausgabe 22. September 2004
Gesehen am 21.05.2024